CULTIVATING REFLECTIVE THINKING SKILLS THROUGH GAMIFICATION IN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) - Yuniasti, Ismaatul; Puspitasari, Yunita; Kusuma, Dewi Indah (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2024)
Reflective thinking enables students to become more self-aware, self-directed, and self-regulated learners, which are critical abilities for attaining success in academic and professional contexts. Choosing the right learning models would enhance students' capacity to think critically and reflect intentionally when they approach a variety of everyday challenges. Student Teams Achievement Division (STAD) enables students to apply their knowledge based on what they have learned and to work cooperatively to solve problems. However, STAD has inevitably drawn much criticism, such as that interdependence may have adverse effects if participants fail to establish any relationship between participation and achievement. This research, thus, integrated gamification in STAD assuming that the manipulation prospectively made significant differences in the students' reflective thinking skills Employing a non-randomized one-group pre-test and post-test design, the questionnaire was administered to collect the data from 15 EFL students of Islamic Junior High School in Jombang. The Wilcoxon signed rank test was run to find out the statistically significant difference between the before and after conditions. The results of the data analysis revealed the obtained value of Sig. was at .003, which means that there was a significant difference in the students' reflective thinking skills before and after the implementation of STAD. Besides, the mean rank value showed that there was an upgrading score from 39.20 to 54.87. Accordingly, STAD is recommended as a prospective learning model to improve the quality of EFL classroom practices and the employment of the Merdeka Curriculum in Indonesia.